A mesoscale approach to simulate residual deformations in complex laser welding processes. (December 2022) - Favaretti, Piero; Parussini, Lucia
Laser welding can be characterized by very small radii of beam, in the order of tenths of a millimeter, and very short high power inputs (more kW in few ms), and thus, it can be certainly classified as a microscale process with a high level of physical complexity. This is clearly incompatible, due to the high computational costs, with the analysis of macroscale processes related to large geometries and non-uniform welding patterns. In order to overcome this issue, a simplified finite element method (FEM)–based thermo-elastoplastic model is presented to simulate heat transfer and residual deformations due to thermal expansion and material plasticity. The idea is to substitute the microscale analysis with a mesoscale approach that renounces to describe in detail all the physical phenomena occurring in the heated zone and focuses attention on the correct prediction of the keyhole depth and weld pool size, that are the most important parameters to describe the mechanical characteristics of the welded joint. The concept of passive element, based on the numerical adjustment of the material properties in order to take into account the orthotropic behavior during the keyhole formation, is introduced. In particular, the new approach has been tested on the pulsed laser welding process of two overlapping DC04 steel plates with thickness of 0.5 mm (so-called sandwich) and validated through experimental tests involving different input parameters, such as power, pulse duration and frequency, speed, and geometrical pattern.